Control of proline accumulation under drought via a novel pathway comprising the histone methylase CAU1 and the transcription factor ANAC055. (14th December 2017) - Fu, Yanlei; Ma, Hailing; Chen, Siying; Gu, Tianyu; Gong, Jiming
Abstract : Expression of CAU1 (encoding a histone methylase) decreases under drought, leading to de-repression of the NAC transcription factor ANAC055 and its genetically downstream proline synthetase gene P5CS1, and this results in proline accumulation and a consequent increase in drought tolerance. Abstract: Proline plays a crucial role in the drought stress response in plants. However, there are still gaps in our knowledge about the molecular mechanisms that regulate proline metabolism under drought stress. Here, we report that the histone methylase encoded by CAU1, which is genetically upstream of P5CS1 (encoding the proline biosynthetic enzyme Δ 1 -pyrroline-5-carboxylate synthetase 1), plays a crucial role in proline-mediated drought tolerance. We determined that the transcript level of CAU1 decreased while that of ANAC055 (encoding a transcription factor) increased in wild-type Arabidopsis under drought stress. Further analyses showed that CAU1 bound to the promoter of ANAC055 and suppressed its expression via H4R3sme2-type histone methylation in the promoter region. Thus, under drought stress, a decreased level of CAU1 led to an increased transcript level of ANAC055, which induced the expression of P5CS1 and increased proline level independently of CAS . Drought tolerance and the level of proline were found to be decreased in the cau1 anac055 double-mutant, while proline supplementation restored drought sensitivity in the anac055 mutant. Our results reveal the details of a novel pathway leading to drought tolerance mediated by CAU1 .